2008
DOI: 10.1186/bcr2119
|View full text |Cite
|
Sign up to set email alerts
|

Continuing trastuzumab beyond disease progression: outcomes analysis in patients with metastatic breast cancer

Abstract: Introduction We performed a retrospective analysis of HER2-overexpressing metastatic breast cancer patients to describe clinical outcomes of those who, despite progression of the disease (PD), maintained trastuzumab for multiple chemotherapy lines. We also compared survival of these patients with that of those who halted trastuzumab at first PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…While a number of retrospective analyses have shown a potential advantage for the "continuation policy" (reviewed in [3][4][5][6]) in agreement with our results, two retrospective studies indicated no statistically significant benefit from continuing trastuzumab [17,6]. In these studies, carried out by the same group, the authors themselves suggest that patients continuing trastuzumab might have been subject to closer clinical evaluation because of the weekly administration schedule of the antibody compared to the control arm of untreated patients, and an earlier detection of disease progression may have partially clouded the benefit of continuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of retrospective analyses have shown a potential advantage for the "continuation policy" (reviewed in [3][4][5][6]) in agreement with our results, two retrospective studies indicated no statistically significant benefit from continuing trastuzumab [17,6]. In these studies, carried out by the same group, the authors themselves suggest that patients continuing trastuzumab might have been subject to closer clinical evaluation because of the weekly administration schedule of the antibody compared to the control arm of untreated patients, and an earlier detection of disease progression may have partially clouded the benefit of continuation.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients may develop resistance to trastuzumab and show metastatic disease progression. Several retrospective studies published thus far (reviewed in [3,4]) [5,6] have indicated a certain overall response rate, clinical benefit and extended time to progression from the use of a second trastuzumabcontaining regimen in HER2-positive MBC patients who progressed on first-line trastuzumab treatment. Moreover, two recent randomized trials designed to directly evaluate the efficacy of continuing trastuzumab after progression demonstrated the potential clinical utility of continuing trastuzumab even for patients with progressive disease [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies (Stemmler et al, 2005;Cancello et al, 2008;Extra et al, 2010) have shown that continuation of anti-HER2 therapies in patients progressing after trastuzumab-based treatment was associated with improved response rates and improved survival in HER2-positive MBC patients. Also in prospective randomized phase III studies (von Minckwitz et al, 2009;Blackwell et al, 2010), trastuzumab combination with capecitabine or lapatinib resulted in improved progression free survival compared to single agent capecitabine or lapatinib.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, options included stopping trastuzumab in favor of chemotherapy, or the more common clinical practice of continuing trastuzumab while changing its chemotherapeutic partner. This was based on empirical and retrospective data suggesting that trastuzumab retains its antitumor activity beyond progression [4,5]. The first randomized trial to confirm these findings was the GBG-26 (trastuzumab beyond progression) study which randomized patients with metastatic Her-2/neu-positive breast cancer, who progressed under first-line trastuzumab-based therapies to capecitabine +/-trastuzumab.…”
Section: Introductionmentioning
confidence: 99%